Challenges in Reaching Medicaid and Medicare Enrollees in a Mailed Fecal Immunochemical Test Program - Green, Beverly B.; West, Imara I.; Baldwin, Laura Mae; Schwartz, Malaika R.; Coury, Jennifer; Coronado, Gloria D. (Journal of community health, 2020)
BeneFIT was a demonstration project that worked with a Medicaid/Medicare health plan to implement a mailed fecal immunochemical test (FIT) program. The goal was to reach age-eligible enrollees who were due for colorectal cancer (CRC) screening and prompt them to complete a FIT. One health insurance plan collaborated with six federally qualified health centers (FQHCs) in Oregon. Reach was defined as the percent of eligible individuals overdue for CRC screening who were mailed a FIT in 2016. We examined patient-level factors associated with reach, using multivariable log binomial regression and FIT completion rates at 6 months. The health plan identified 3386 age-eligible members overdue for CRC screening. Of these, 2615 (77.2%) were reached (mailed FIT kits) and 771 (22.8%) were not; 478 (14.1%) because they were not considered to be clinic patients and 290 (8.6%) because of mailing issues. Patient-level factors associated with not being reached were: being male, being Medicaid-insured (vs. Medicare), and having no primary care visits (vs. 4+ visits) in the last year. Among all enrollees identified as overdue for CRC screening, FIT completion rates at 6 months were 14.8% overall and 18.5% in the subgroup reached. In a mailed FIT program, a health insurance plan attempted to reach as many enrollees overdue for CRC screening as possible, however 22.8% were not mailed a FIT. Additional efforts are needed to ensure that the hardest to reach enrollees can participate in CRC screening.